A content validity: Organisational performance’s assessment instrument in the construction industry - Khairul Firdaus, Anuar; Nurhaizan, Mohd Zainudin; Muhammad Ashraf, Fauzi (Universiti Teknologi MARA, 2024)
Evaluating the performance of construction organisations is crucial for the success of construction projects. However, there are no standardized instruments and a single way to measure how well construction organisations perform, making it difficult for researchers and practitioners to get a clear picture of their performance. This study aims to validate an instrument for assessing the organisational performances of construction organisations through content validity. A panel of eight (8) experts reviewed the instrument, rating the relevance of each item to the concept of organisational performance. The Content Validity Ratio (CVR) results showed that twenty-one (21) of fifty-two (52) items were considered the most critical by the content experts, and the results for the Item Level Content Validity Index (I-CVI) showed that forty-six (46) items were considered appropriate. These findings demonstrate that the instrument has adequate content validity. The outcomes of this study have important implications for the use of this instrument in organisational performance assessment for the construction industry. The instrument can be used to measure construction organisational performance comprehensively and systematically. This will help researchers and practitioners better understand the factors that contribute to performance and develop interventions to improve it.